Cases Of Rectum Cancer Patients Based On Characteristics (Literature Study) - Riska Yunisyah Zainal; Rahmawati, Rahmawati; Irwan Wijaya (Jurnal EduHealth, 2024)
Colorectal or rectal cancer is cancer that grows and develops in the rectum or what is better known among the public as the large intestine or rectum. Studies conducted so far have provided evidence that rectal cancer sufferers are increasing every year. However, although there has been several studies on rectal cancer in Indonesia, including in the Makassar region, there are still significant knowledge gaps that need to be filled. Quantitative research method with a literature review approach. The results and conclusions of research found from 20 journals or articles show that the characteristics of rectal cancer patients can be categorized as age, gender, lifestyle and management.